Identification of Naturally Occurring Cartilage Damage in the Equine Distal Interphalangeal Joint Using Low-Field Magnetic Resonance Imaging and Magnetic Resonance Arthrography - van Zadelhoff, Claudia; Schwarz, Tobias; Smith, Sionagh; Engerand, Antoine; Taylor, Sarah (Frontiers in Veterinary Science, 2020)
Objectives: To describe detectable and non-detectable naturally occurring cartilage damage of the equine distal interphalangeal joint using plain magnetic resonance (MR) imaging and gadolinium and saline MR arthrography. The second objective was to quantify the sensitivity, specificity and accuracy in detection of cartilage damage. Methods: In a pilot study, the distal limbs of two horses with confirmed osteoarthritis of the distal interphalangeal joint were imaged with low-field MR. MR images were assessed in consensus by three observers and compared to gross pathological findings. Subsequently, a prospective analytical cross-sectional study design was created to compare pre-contrast magnetic resonance (MR) imaging and saline and gadolinium MR arthrography of isolated equine distal limbs to gross observation findings. Hallmarq® low-field MR (0.27T) scans were performed prior to DIP joint injection, saline/gadolinium post-injection scans were performed at 15 min intervals for 2hrs. Joints were inspected, and the articular cartilage graded subjectively for cartilage damage (0-3). The presence of detectable or non-detectable cartilage damage on MR images was identified, characterized and recorded in consensus by three observers. Sensitivity, specificity and accuracy in detection of cartilage damage related to gross pathology were calculated. Results: The two clinical cases from the pilot study with confirmed osteoarthritis had full thickness cartilage defects however only one of these was correctly identified using low field MRI. In the prospective study, the majority of naturally occurring cartilage damage could not be identified on plain MR or MR arthrography including extensive partial thickness cartilage erosions. Only substantial or full thickness cartilage defects were detectable in some cases. Saline and gadolinium MR arthrography did not improve the detection of cartilage damage. The accuracy of cartilage damage detection was 0.63 with a sensitivity of 0.14 and specificity of 0.92. Clinical relevance: Both, plain low field MRI and MR arthrography are not sensitive in detection of naturally occurring cartilage damage of the distal interphalangeal joint. However, if an abnormal contour is seen in the articular cartilage, cartilage damage is likely to be present.